2012
DOI: 10.1002/app.36782
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel membranes based on gum tragacanth with tunable structures and properties. II. Comprehensive characterization of the swelling behavior

Abstract: Hydrogel membranes based on gum tragacanth (GT), with a wide range of crosslinking densities (0.83-23.87 Â 10 À6 mol/cm 3 ) and swelling capacities (120-1580 g/g), were prepared with the aid of heat alone and four crosslinking reagents according to a procedure reported in our previous article. In this article, we report on the comprehensive evaluation of the swelling behavior of the prepared hydrogel membranes. These include the swelling kinetics, swelling behavior in terms of the pH and ionic strength of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…As shown in Table , the water absorbency was quite low at a neutralization degree of 65% and higher at a neutralization degree of 70%; this was caused by the increase in the ionic dissociation of the carboxylic acid groups . The maximum absorbency (1701 g/g in distilled water and 388 g/g in 0.9 wt % NaCl solution) were obtained when the neutralization degree of AA was 85%.…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Table , the water absorbency was quite low at a neutralization degree of 65% and higher at a neutralization degree of 70%; this was caused by the increase in the ionic dissociation of the carboxylic acid groups . The maximum absorbency (1701 g/g in distilled water and 388 g/g in 0.9 wt % NaCl solution) were obtained when the neutralization degree of AA was 85%.…”
Section: Resultsmentioning
confidence: 94%
“…The physical, chemical and biological properties of TG including structure, thermal behavior, emulsifying, viscosity, acidity, stability, and also rheological, antibacterial, biocompatibility and biodegradability have been reported by various researchers [2,4,6,10,12,[18][19][20][21]. In recent years, several works are reported on the application of TG in the wound and burn dressing [22], synthesis of silver nanoparticles [2], hydrogel membranes [20], superabsorbent hydrogel [3,23] matrix of verapamil hydrochloride tablets [24], matrix for cell immobilization [10] and drug encapsulation [5,25,26].…”
Section: Introductionmentioning
confidence: 97%
“…In the pharmaceutical industry, it is used as a suspending agent in oil-in-water emulsions, jellies and toothpastes, as a stabilizer in dermatological creams and lotions as well as a binding agent in the production of drug tablets (31). Since the past decade, this gum has been investigated as a retarding agent for sustained release of drugs (38) and membranes with possible application in drug delivery systems (39,40). Recently, Fattahi et al (41) showed that physically cross-linked ferric-tragacanth gels exhibit better cell adhesion properties compared to physically cross-linked ferric-alginate gels.…”
Section: Introductionmentioning
confidence: 99%